Preschool Children Differentiation According to the Lingua- Grammatical Categories Development - Z. V. Polivara (Russian State Vocational Pedagogical University, 2015)
The parallel existence of languages and cultures brings forward the necessity of studying this linguistic phenomenon and designing special methods of speech development for the bilingual children. The particular attention should be given to the preschool age, for according to A. A. Leontyev's study, the parallel acquiring of two languages often results in insufficient development of socio-linguistic speech standards. The research is devoted to the phenomenon of the two language systems coexistence in a bilingual person's consciousness, both of them functioning and encoding the same subjects and phenomena. The peculiarities of language interference are described with the reference to the Russian-Tatar bilingual environment. The author believes that the bilingual interference problems are not caused by the phonetic and grammar system differences of the two languages. To find out the potential source of inter-language transition and interrelations between the native and non-native languages, it is necessary to identify the cognitive, neurolinguistic and psycho-linguistic aspects. Therefore, the regional phenomenon of mass bilingualism among the Tatar population is examined by the author in the framework of the psycho-linguistic and cognitive approaches. The paper presents the model of the lexical and grammar categories formation based on differentiated preschool teaching of the bilingual children. The proposed model makes it possible to overcome the limited viewpoint on the general speech dysfunctions, as well as the specifics of lexical and grammar categories development. It can be used for the further development of educational programs in psycho-linguistics, ethno-linguistics, onto-linguistics, cognitive linguistics, social-linguistics, contrastive linguistics and the language theory by means of extending the teaching course content.